The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/bios11050133
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Aptasensor for Instantaneous Determination of Cadmium Ions Based on Fluorescence Amplification Effect of MOPS on FAM-Labeled Aptamer

Abstract: Analytical performance and efficiency are two pivotal issues for developing an on-site and real-time aptasensor for cadmium (Cd2+) determination. However, suffering from redundant preparations, fabrications, and incubation, most of them fail to well satisfy the requirements. In this work, we found that fluorescence intensity of 6-carboxyfluorescein(FAM)-labeled aptamer (FAM-aptamer) could be remarkably amplified by 3-(N-morpholino)propane sulfonic acid (MOPS), then fell proportionally as Cd2+ concentration int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The investigative enzymes like CAT, POD, APX and SOD perform an essential function in the metabolic responses of environmental stress function in crop [ [53] , [64] , [71] ]. Liu et al [ 72 ] reported that the increased in the activities of SOD and CAT in Si treated plants present enhanced modification of O to H 2 O 2 as similar to Si treatment in Refs. [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The investigative enzymes like CAT, POD, APX and SOD perform an essential function in the metabolic responses of environmental stress function in crop [ [53] , [64] , [71] ]. Liu et al [ 72 ] reported that the increased in the activities of SOD and CAT in Si treated plants present enhanced modification of O to H 2 O 2 as similar to Si treatment in Refs. [ 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The quenching efficiency was determined by the formula ( F 1 − F 0 )/ F 1 , where F 1 and F 0 are the fluorescence signals of ATP aptamers before and after adding GO. 31 The signal-to-noise ratio (SNR) was determined by the formula SNR = F / F 0 , where F represents the recovered fluorescence intensity and F 0 is the quenched fluorescence intensity before adding the target compounds. 32 The correlation between GO concentration and quenching efficiency was obtained by recording the plateau quenching at different GO concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence quenching efficiency was calculated using the formula below [ 47 ]: where F PC is the emission intensity of SQ-122 PC, and F dye is the emission intensity of the SQ-122 dye at the same concentration in H 2 O (30%).…”
Section: Methodsmentioning
confidence: 99%